Transient perivascular inflammation of the carotid artery (TIPIC) syndrome in a patient with COVID-19. (July 2021) - Mumoli, Nicola; Evangelista, Isabella; Colombo, Alessandra; Conte, Giulia; Mazzone, Antonino; Barco, Stefano
Highlights: Transient perivascular inflammation of the carotid artery (TIPIC) is a rare condition. TIPIC is characterized by typical ultrasonographic findings and local pain. A case of TIPIC in a patient who was recently diagnosed with COVID-19 is described.